Microbial necromass response to soil warming: A meta-analysis - Mitchell, Megan F.; MacLean, Meghan Graham; DeAngelis, Kristen M. (Frontiers in Soil Science, 2022)
Microbial-derived soil organic matter (SOM), or necromass, is an important source of SOM and is sensitive to climate warming. Soil classification systems consider soil physicochemical properties that influence SOM, hinting at the potential utility of incorporating classification systems in soil carbon (C) projections. Currently, there is no consensus on climate warming effects on necromass and if these responses vary across reference soil groups. To estimate the vulnerability of necromass to climate warming, we performed a meta-analysis of publications examining in situ experimental soil warming effects on microbial necromass via amino sugar analysis. We built generalized linear models (GLM) to explore if soil groups and warming methodologies can be used to predict necromass stocks. Our results showed that warming effect sizes on necromass were not uniform across reference soil groups. Specifically, warming effect sizes were generally positive in permafrost soils but negative in calcic soils. However, warming did not significantly change average necromass. Our GLMs detected significant differences in necromass across soil groups with similar texture and clay percentage. Thus, we advocate for further research to define what predictors of necromass are captured in soil group but not in soil texture. We also show warming methodology is a significant predictor of necromass, depending on the necromass biomarker. Future research efforts should uncover the mechanistic reason behind how passive versus active warming methodology influences necromass responses. Our study highlights the need for more in situ soil warming experiments measuring microbial necromass as this will improve predictions of SOM feedback under future climate scenarios.